CRISIS LEADERSHIP IN DEALING WITH THE COVID-19 PANDEMIC: A SYSTEMATIC LITERATURE REVIEW STUDY - Christianingrum; Syamsul Hadi Senen; Rofi Rofaida; Emi Amelia (Fakultas Ekonomi, Universitas Negeri Jakarta, 2023)
This research aims to uncover articles published on crisis leadership during the COVID-19 pandemic. The study employs a systematic literature review approach by analyzing articles published between 2020 and 2022. Initially, a total of 979 articles were identified, which were then narrowed down to 29 articles based on inclusion and quality criteria. The extracted results regarding crisis leadership issues during the COVID-19 pandemic are categorized into 4 major journal groups: management and leadership, health, social, and education journals. Emerging issues within crisis leadership include gender post COVID-19, academic leadership, administrative leadership, public health leadership, digitalization & virtual leadership, fault lines of leadership, and leadership approach. The changes in crisis leadership have led to the emergence of new leadership strategies, such as virtual collaboration across boundaries.